2021
DOI: 10.26434/chemrxiv.13252544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In situ X-ray Diffraction Investigation of the Crystallisation of Perfluorinated Ce(IV)-based Metal-Organic Frameworks with UiO-66 and MIL-140 architectures

Abstract: We report on the results of a thorough <i>in situ</i> synchrotron powder X-ray diffraction study of the crystallisation in aqueous medium of two recently discovered perfluorinated Ce(IV)-based metal-organic frameworks (MOFs), analogues of the already well investigated Zr(IV)-based UiO-66 and MIL-140A, namely, F4_UiO-66(Ce) and F4_MIL-140A(Ce). The two MOFs were originally obtained in pure form in similar conditions, using ammonium cerium nitrate and tetrafluoroterephthalic acid as building blocks, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Our previous work showed that, due to the similarities between the PXRD patterns of the fcu and hcp MOFs, 16,54 it is not always immediately obvious that a MOF structure with a different cluster has formed. Despite advances in understanding, [56][57][58] including studies on the effects of different variables (including acid modulator and water) on the crystallisation of UiO-66(Zr) 41 (and cerium analogues 59 ), a full picture of the formation routes of MOFs -in particular the precrystalline stages of cluster growth -is still far off. In our work on UiO family MOFs, in situ measurements to probe crystallisation of the hcp phase suggested that inorganic (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work showed that, due to the similarities between the PXRD patterns of the fcu and hcp MOFs, 16,54 it is not always immediately obvious that a MOF structure with a different cluster has formed. Despite advances in understanding, [56][57][58] including studies on the effects of different variables (including acid modulator and water) on the crystallisation of UiO-66(Zr) 41 (and cerium analogues 59 ), a full picture of the formation routes of MOFs -in particular the precrystalline stages of cluster growth -is still far off. In our work on UiO family MOFs, in situ measurements to probe crystallisation of the hcp phase suggested that inorganic (i.e.…”
Section: Introductionmentioning
confidence: 99%